Study and Assess the Occupation Hazards to Health Workers in the City of Kut/ Wassit - Fatima Haran Daham1 , Alaa Kadhim Jasim 2 , Khalied Yassen Zakair3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Occupational hazards are a major medical, social, economic problem and a leading cause ofmorbidity and mortality for health workers. The aims of this study was to identify the types of occupationalhazards and risks that health workers are exposed to in the study area. In addition, to measure risk level ofoccupation hazards. This is a cross sectional descriptive study was carried out among health workers in twohospitals located in Kut city in Wasit governorate. The period of the study extended from October 2019, untilthe end of March 2020. Data collected by using questionnaire form. The occupation hazards dimensions,which include four domains: physical hazards, chemical hazards, biological hazards, and psychologicalhazards. The statistical methods used included Chi-square and Fisher exact test. A statistical significantassociation (p<0.05). The main findings of the current study indicate that the commonest occupationalhazards among the health workers in Al- Kut hospital was noise (58.6%), and the second hazard in thiscategory was fire (51.9%). While in Al-Karamah hospital the commonest occupational hazards among thehealth workers was noise (57.9%) . Conlusively, the study was found that health workers in Al-Karamahhospital had experienced light, heat, noise, psychological, and chemical hazard higher than health workersin Al-Kut hospital. In addition , the health workers in Al-Karamah hospital had experienced biological lowerthan health workers in Al-Kut hospital.